In Vitro Fertilization Is Successful in Women With Ulcerative Colitis and Ileal Pouch Anal Anastomosis. (June 2015) - Pabby, Vikas; Oza, Sveta Shah; Dodge, Laura E; Hacker, Michele R; Moragianni, Vasiliki A; Correia, Katherine; Missmer, Stacey A; Fox, Janis H; Ibrahim, Yetunde; Penzias, Alan; Burakoff, Robert; Cheifetz, Adam; et al.
Abstract : Background: Women with ulcerative colitis (UC), who require ileal pouch anal anastomosis (IPAA), have up to a threefold increased incidence of infertility. To better counsel patients who require colectomy, we examined the success rates of in vitro fertilization (IVF) among women who have undergone IPAA. Methods: This was a retrospective cohort study conducted at the Brigham and Women's Hospital and Beth Israel Deaconess Medical Center. Female patients with UC were identified via ICD‐9 codes and cross‐referenced with those presenting for IVF from 1998 through 2011. UC patients with IPAA were compared with the following two unexposed groups that underwent IVF: (1) patients with UC, who had not undergone IPAA, and (2) patients without inflammatory bowel disease (IBD). The primary outcome was the cumulative live birth rate. Secondary outcomes included number of oocytes retrieved, proportion of patients who underwent embryo transfer, pregnancy rate, and live birth rate at first cycle. Results: There were 22 patients with UC and IPAA, 49 patients with UC and without IPAA, and 470 patients without IBD. The cumulative live birth rate after six cycles in the UC and IPAA groups was 64% (95% confidence interval (CI): 44–83%). This rate did not differ from the cumulative live birth rate in the UC without IPAA group (71%, 95% CI: 59–83%; P =0.63) or the group without IBD (53%, 95% CI: 48–57%; P =0.57). Conclusions: This study demonstrates that in our cohort, women who undergo IPAA achieve live births following IVF at comparable rates to women with UC without IPAA and to women without IBD.